Militansi caleg muda dalam pemenangan pemilu tahun 2019 di kabupaten aceh barat - Syamsuar, Syamsuar; Andini, Mirna Ria (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2020)
The communication strategy (militancy) in politics is one of the keys to the success of a political party (Parpol) or Legislative Candidates (Caleg) in winning the Election. In the 2019 Election at the West Aceh DPRK level, there were many political figures from young people who ran to become members of the legislature at the district level. These political figures are referred to as Young Candidates who are between 21 and 30 years old. Several young candidates at the DPRK West Aceh level won the 2019 Election. This research is qualitative with a descriptive method. The purpose of this research is to find out how the strategies of young candidates at the West Aceh DPRK level in winning the 2019 election and the obstacles they face in building a political communication strategy. The results obtained are that young candidates at the DPRK West Aceh level use interpersonal communication strategies or direct communication that use family and acquaintances to get votes in the election. In addition, young candidates at the DPRK West Aceh DPRK level use mass media only a little, they only use social media which is not paid. Having no experience in politics is the biggest obstacle in the candidacy of young candidates at the West Aceh DPRK level.Keywords: Strategy; Communication; Political; Young Candidates.